Targeted Disruption of Chlamydia trachomatis Invasion by in Trans Expression of Dominant Negative Tarp Effectors - Parrett, Christopher J.; Lenoci, Robert V.; Nguyen, Brenda; Russell, Lauren; Jewett, Travis J. (Frontiers in Cellular and Infection Microbiology, 2016)
Chlamydia trachomatis invasion of eukaryotic host cells is facilitated, in part, by the type III secreted effector protein, Tarp. The role of Tarp in chlamydiae entry of host cells is supported by molecular approaches that examined recombinant Tarp or Tarp effectors expressed within heterologous systems. A major limitation in the ability to study the contribution of Tarp to chlamydial invasion of host cells was the prior absence of genetic tools for chlamydiae. Based on our knowledge of Tarp domain structure and function along with the introduction of genetic approaches in C. trachomatis, we hypothesized that Tarp function could be disrupted in vivo by the introduction of dominant negative mutant alleles. We provide evidence that transformed C. trachomatis produced epitope tagged Tarp, which was secreted into the host cell during invasion. We examined the effects of domain specific Tarp mutations on chlamydial invasion and growth and demonstrate that C. trachomatis clones harboring engineered Tarp mutants lacking either the actin binding domain or the phosphorylation domain had reduced levels of invasion into host cells. These data provide the first in vivo evidence for the critical role of Tarp in C. trachomatis pathogenesis and indicate that chlamydial invasion of host cells can be attenuated via the introduction of engineered dominant negative type three effectors.